Neoplastic Diseases of the Blood (Springer International Publishing, 2018)
The new edition of this textbook integrates the history, epidemiology, pathology, pathophysiology, therapeutics, and supportive care of modern neoplastic hematopathology. Now in its sixth edition, this classic and invaluable text brings together a team of internationally renowned experts and offers in-depth coverage of the complex interface between diagnosis and therapy. The textbook is divided into five major sections, with the first four covering the spectrum of hematologic neoplasia, including chronic leukemias and related disorders, acute leukemias, myeloma and related disorders, and lymphomas, and the fifth section covering a variety of topics in supportive care. Chapters are presented in an accessible and easy-to-read layout, providing updates on the tremendous progress made in the last decade in the understanding of the nature of hematologic malignancies and their treatment. Neoplastic Diseases of the Blood, Sixth Edition is an authoritative and indispensable resource for students, trainees, and clinicians, sure to distinguish itself as the definitive reference on this subject.